Impact evaluation of the Brazilian non-contributory pension program BPC (Benefício de Prestações Continuada) on family welfare - Oliveira, Pedro Rodrigues de (2012)
This study evaluates the eect of the Benefcio de Prestac~ao Continuada (BPC) program on family welfare. The program is targeted to poor disabled and elderly people providing monthly stipends equal to one monthly minimum wage. The establishment of an age at which the person becomes eligible for the benet created a discontinuity in the probability of being treated which is explored for identication. We developed a procedure to decompose the stipends from social programs using the PNAD dataset, thereby identifying which programs the person participates. Therefore, from 2001 to 2008 we estimate the eect of the BPC on variables such as household composition, labor force participation, weekly worked hours { for the elder and co-residents { besides child labor and school attendance. We found that the program have signicant eects on child labor reduction, on labor force participation for members between 30 and 49 years-old, and on the number of members between 30 and 59 years-old. It was also observed an expected labor force participation reduction for the elderly, but no eects on school attendance of children. No signicant eects on worked hours were found. The complexity of the ndings highlights the need of studying the heterogeneity of social cash transfers, where many latent aspects are yet to be uncovered.